O acompanhante especializado na inclusão escolar de autistas: contribuições psicanalíticas - Schultz, Joice (2019)
The theme of this study centers on the activity of accompanying professionals in the inclusion of autistic students. The main objective was to investigate the contributions of psychoanalysis to the activity of these professionals. We investigated how the activity of the accompanying professional, in inclusive autistic education, might contribute to the autism's subject constitution. We conducted a literature review of theses, dissertations, and articles available in the following scientific databases: BVS-PSI, Bireme, Lilacs, SciELO, CAPES, PEPSIC, and BDTD. The themes covered included specialized companion, accompanying professional, support teacher, support professional, autism, inclusive education, and psychoanalysis. We did not identify researches that discussed our object of study in the light of psychoanalysis. As theoretical and methodological references, we adopted the historical and dialectical materialism in order to identify and analyze the contradictions, possibilities, and limitations of the Brazilian educational system regarding inclusive public policies of autistic students. This is a qualitative research that analyze documents about the performance of the accompanying professional of autistic individuals in school inclusion. We cover the historical and social trajectory of inclusion of autistic students in the Brazilian regular education system in order to understand how the hegemonic thinking on autism in special education was materialized, based on medical knowledge. Thus, we investigated how the production of knowledge about mental disability in the field of medical knowledge has contributed, over time, to a biological conception on autism that has become hegemonic in the educational field. We observed that the hegemonic discourse about autism, based on medical knowledge, functions as an ideology. This occurs because - under the guise of neurobiological origins - the discourse hinders the importance of the social environment for autistic development. Moreover, we cover autism as an ontological category, a perspective allowed by psychoanalysis. Subsequently, we explored how occurs the constitution of the subject in the light of autism, intending to understand the autistic way of being, identifying - in the accompanying professional-autistic student relationship, the conditions for a subjective constitution of this student. We realize that, in autism, the constitution of the subject fails. As a result, for the autistic, there is no symbolic register in the realms of language, which impedes the subject from being launched into the world of communication. This flaw, in addition to genetic and neurobiological aspects, also occurs as a result of a primary nonrecognition between mother and child. For this recognition to happen, it is necessary for someone to lend their desire, so that the traits and signs are accessible to the autistic individual. In schools, we suggest that this should be the first role of the accompanying professional, so that he or she can lend desires and, with effort, that this activity goes beyond the caregiver role, extending their functions to the point where the autistic student can recognize itself in this relationship. We therefore present some possibilities for this recognition to happen in the accompanying professional-autistic student relationship. The results indicate that the recognition of the autistic individual in the companion of an accompanying professional enables learning. In this sense, we defend an education that recognizes autists as subjects of language, which aims to overcome a view on teaching - currently centered on the hegemonic medical and pedagogical model - based on biological factors to explain school failure.